Recent research trend of micro hot-embossing - Lee, Seung Hyun; Jo, Jeongdai; Kim, Kwang Young; Choi, Young Man (Journal of the Korean Society for Precision Engineering, 2018)
Micro hot-embossing is a powerful tool in the agile additive manufacturing industry. Its applications include optical components, micro-fluidic devices, MEMS, hydrophobic/hydrophilic surfaces, and energy harvesting devices. To overcome a drawback of low-process speed, the R2R process has been innovated, with novel embossing mechanisms and process optimization. Also, new materials beyond thermoplastic polymers have been applied to develop new devices, or enhance device performance. This review surveys recent progress in micro hot-embossing technology, in terms of new mold fabrication process, process innovation, and various applications.
Keywords: Hot embossing; Micro patterning; Patterning mold; Thermal imprinting